Diagnostic performance of the SD Bioline Malaria Ag Pf® rapid diagnostic test for malaria screening among school-aged children in Mbujimayi, Democratic Republic of the Congo - Yamba Mukendi, Alain; Kabongo-Tshibaka, Augustin; Kalala-Tshituka , Nestor; Ndjibu-Mpoji, Faustin; Lufuluabu Mpemba, Alphonse; Ngombo Katende, Bernard; Cindibu Kalonji, Florence; Cimuanga-Mukanya , Alain; Likwela Losimba, Joris; Tshibangu Kabamba, Evariste; Kayiba-Kalenda, Nadine (Orapuh Journal, 2026)
Introduction School-aged children in malaria-endemic regions often harbour asymptomatic and low-density infections, constituting a hidden reservoir that complicates malaria control efforts. Although rapid diagnostic tests (RDTs) provide a practical screening tool, data on their diagnostic accuracy in this population remain limited. Purpose This study aimed to assess the diagnostic accuracy of the SD Bioline Malaria Ag Pf® RDT among school-aged children and to generate evidence to support malaria surveillance and control strategies in Mbujimayi. Methods A cross-sectional survey was conducted in February 2023 among 494 students aged 5–12 years from two primary schools in Mbujimayi, Democratic Republic of the Congo. Capillary blood samples were collected for thick and thin blood smears and SD Bioline Malaria Ag Pf® testing. Sensitivity, specificity, positive and negative predictive values (PPV and NPV), Cohen’s kappa coefficient, and receiver operating characteristic (ROC) curve analysis were used to evaluate RDT performance relative to microscopy. Results The median age of the children was 10 years (range: 4–15 years). The prevalence of malaria was 27.3% (95% CI: 23.5–31.4) by both thick blood smear microscopy and the SD Bioline Malaria Ag Pf® RDT. Plasmodium falciparum accounted for 97.0% of infections. Agreement between the two diagnostic methods was fair (κ = 0.38; p = 0.001). The RDT demonstrated a sensitivity of 57.3% and a specificity of 87.1%, with a PPV of 47.2% and an NPV of 91.1%. The area under the ROC curve was 0.715 (95% CI: 0.663–0.767). The optimal parasite density threshold for detection was 202 parasites/µL, corresponding to a sensitivity of 52% and a specificity of 91%. Conclusion Among school-aged children, the SD Bioline Malaria Ag Pf® RDT demonstrated moderate diagnostic performance, reliably detecting moderate-to-high parasitaemia but missing a substantial proportion of low-density infections. Complementary diagnostic approaches may therefore be required to accurately identify malaria infections in this age group.